First evidence of immunomodulation of the renin-angiotensin system through substance P/neurokinin 1 receptor: a case and control study in hypertension and cardiac patients - Ibrahim M. Alanazi; Riffat Mehboob; Ayesha Tariq; Sajid Hameed; Uzma Malik; Noreen Sarwar; Imran Shahid; Khurram Mehboob (Italian Journal of Medicine)
Gaining knowledge about the differences in substance P (SP) and neurokinin 1 receptor (NK1R) levels between cardiac and hypertensive patients may help clarify how these neuropeptides could be involved in the pathophysiology of cardiovascular disorders. This study aimed to investigate the levels of SP and NK1R in individuals diagnosed with hypertension and cardiac conditions. Participants were chosen from a pool of hypertensive (n=30) and cardiac patients (n=35) in addition to a control group (n=12). Each participant was asked for their informed permission before any demographic data, medical history, and pertinent clinical data were gathered. Serum samples were obtained, and the levels of SP and NK1R were measured using the enzyme-linked immunosorbent assay. When compared to the control group, the levels of SP and NK1R in hypertension patients were considerably higher. The findings point to a possible link between SP/NK1R and hypertension. There was a noticeably greater percentage of men (68.6%) among cardiac patients. The levels of SP and NK1R in cardiac patients and the control group did not vary significantly. Among those with hypertension and cardiac diseases, smoking, family history, and a diet heavy in salt were the most common risk factors. The study discovered substantial variations in SP and NK1R levels between hypertensive patients and a control group, suggesting a link between these neuropeptides and hypertension. In the case of cardiac patients, however, no significant variations in SP and NK1R levels were identified as compared to the control group.